A Q&A with Bront Palarae at the backstage / Nazima Versay Kudus and Lim Teck Heng - Versay Kudus, Nazima; Lim, Teck Heng (Academy of Language Studies, 2022)
The Integrated Language Skills III (ELC231) code and the English Language Club of UiTMCPP had collaborated in organising a programme, with an outstanding Malaysian actor, Bront Palare. The objective of the session was to encourage students to gain some insights on the movie industry which can inspire them to prepare for their Oral Commentary of Film component of the code. The one-hour session was held on November 6, 2021 from 10.00 a.m. to 11.00 am. It was hosted by the English Language Club President, Mr. Syed Amir Haikal, who is also a student enrolled in the ELC231 code for this semester. The session began with welcoming words from the Head of Department of the Academy of Language Studies, Dr Hajah Rofiza Aboo Bakar. The following is the transcript of the interview.